2014
DOI: 10.3389/fphy.2014.00079
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic quantum optimization for associative memory recall

Abstract: Hopfield networks are a variant of associative memory that recall patterns stored in the couplings of an Ising model. Stored memories are conventionally accessed as fixed points in the network dynamics that correspond to energetic minima of the spin state. We show that memories stored in a Hopfield network may also be recalled by energy minimization using adiabatic quantum optimization (AQO). Numerical simulations of the underlying quantum dynamics allow us to quantify AQO recall accuracy with respect to the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…We previously verified the principles of CAM recall by adiabatic quantum optimization using numerical simulations to investigate the pure-state dynamics of a small memory system [28]. Through simulations of the quantum dynamics, we showed that specific key-value associations could be recovered when the ground state of an encoded Ising model Hamiltonian was prepared by adiabatic quantum optimization.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously verified the principles of CAM recall by adiabatic quantum optimization using numerical simulations to investigate the pure-state dynamics of a small memory system [28]. Through simulations of the quantum dynamics, we showed that specific key-value associations could be recovered when the ground state of an encoded Ising model Hamiltonian was prepared by adiabatic quantum optimization.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the input value is then recalled as opposed to stored memory. This critical value can be calculated based on the Hamming distance between the stored memories [28,34]. For a given problem instance, we recover the lowest energy eigenstate of H θ using AQO.…”
Section: Cam Recall Using Adiabatic Quantum Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The full embedding of a problem graph in the hardware graph is found by first embedarXiv:1612.07366v1 [math-ph] 21 Dec 2016 ding into a chosen virtual hardware or one of its minors. Our choice of a bipartite virtual representation for the hardware is motivated in part by the simplicity of the structure as well as its balance between size and order of the virtual representation, and additionally for its connection to associative memory recall and other variants of machine learning applications [21]. We note that alternative virtual representations are equally valid, e.g., a square grid.…”
Section: Introductionmentioning
confidence: 99%